Educação ambiental em cursos de administração do estado do Rio Grande do Norte - Enéas, Ana Paula de Sousa (Universidade Federal Rural do Semi-Árido, 2016)
The environmental issue in modern organizations today occupies a large portion of the efforts of administrators, demanding a new professional profile that can articulate and organize an organizational structure linking all sectors of organizations towards social and environmental responsibility. Therefore forming committed managers with environmental issue and active in organizations constitutes a challenge for Higher Education Institutions (HEI), being essential that students of Administration courses have in their curricula focused disciplines on environmental issues, because these issues are of utmost importance in academic circles. Therefore, the objective of this study was to analyze how the environmental issue is worked in Management courses in Higher Education Institutions of Rio Grande do Norte State, as environmental education, through their theoretical contributions, opens a stimulating space for a rethinking of social practices and the role of educators. For this, it was performed a multi-case study of a descriptive nature, and how data collection procedures were conducted documentary research, by analyzing the PPCs of the courses and the interview with the coordinators of the courses and professors. 22 RN state administration courses were surveyed, with the total of 22 interviewed coordinators, and each coordinator indicated a business school professor to participate in the interview, with a number of 22 professors. Besides the interviews, the PPCs of the courses were analyzed, however were available only 9 documents. The survey results show that, despite the existence of initiatives that address environmental issues in the surveyed courses, it is noticed that they occur in isolation and limited way to teachers who have closer ties or involvement with the theme, not being held in an interdisciplinary and transverse way across disciplines and activities of the courses, as recommended by the environmental education legislation. For this, it is recommended that there is a collective construction around the theme of the administration courses with their IES and everyone involved, such as employees, professors and students, so that has not been the risk of discontinuity of actions
Environmental educations in administration courses in the state of Rio Grande do Norte
Keywords: Ensino Superior; Coordenadores; Professores; Projetos Pedagógicos dos Cursos; Legislação; Higher Education; Coordinators; Professors; Pedagogical projects of the courses; Legislation; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE